-5(-8+8x)=-3+3x

Simple and best practice solution for -5(-8+8x)=-3+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-8+8x)=-3+3x equation:


Simplifying
-5(-8 + 8x) = -3 + 3x
(-8 * -5 + 8x * -5) = -3 + 3x
(40 + -40x) = -3 + 3x

Solving
40 + -40x = -3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
40 + -40x + -3x = -3 + 3x + -3x

Combine like terms: -40x + -3x = -43x
40 + -43x = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
40 + -43x = -3 + 0
40 + -43x = -3

Add '-40' to each side of the equation.
40 + -40 + -43x = -3 + -40

Combine like terms: 40 + -40 = 0
0 + -43x = -3 + -40
-43x = -3 + -40

Combine like terms: -3 + -40 = -43
-43x = -43

Divide each side by '-43'.
x = 1

Simplifying
x = 1

See similar equations:

| 66+20x=400+66x | | 3x^3-6x^2-15X+18=0 | | 66+20x=400+6x | | 5x-3+2x+5=9x+6 | | 3=1.2+-0.2y | | 14x^3-8x^2+18x= | | -25=5(a-8) | | (x-30)(x-30)(x-30)=540 | | 3x+4+3x-6=8x+4 | | -14=-6+4e | | 29=-x+7x-1 | | 3x+5+3x-6=10x-2 | | 2=1.2+-0.2y | | 30x+5=64 | | 1=1.2+-0.2y | | 42x^2-480x-2463=0 | | 120+.30x=80+.50x | | x+2y-1=6x-9 | | -4m+13=9 | | 3+6cosx=0 | | u^2+u-21=0 | | -6m-13=163 | | 6+0.4x=18+.02 | | 4(-2m-5)+8m=-15 | | 287+49m+7n=-64+4m-2n | | 322-(-159)+10-159+78= | | 39x^2-482x-2464=0 | | X+(x+3)=61 | | 2x-4=3x+12 | | .06+.04x=18+.02 | | 8(b+7)=0 | | y=-4*-4+2*-4-7 |

Equations solver categories